Geospatial Examination of Infrastructure Development in Maharashtra: A Comprehensive Analysis (International Journal of Food and Nutritional Sciences, 2022)
Infrastructure is the basic physical and organizational structures needs for the operation ofsociety or enterprise, or the services and facilities necessary for an economy to function. The termtypically refers to the technical structures that support a society, such as roads, water supply,sewers, power grids, telecommunications and so forth viewed functionally, infrastructure facilitatethe production of goods and services; for example, roads enable the transport of raw materials to afactory, and also for the distribution of finished products to markets. In some contexts, the termmay also include basic social services such as schools and hospitals